EKSEKUSI NAFKAH ANAK PASCA PERCERAIAN DI PENGADILAN AGAMA JAKARTA TIMUR - Virina Abiyyutsani (2021)
This study aims to analyze the practice of Child living expense execution after divorce at the East Jakarta Religious Court. This study is using qualitative research with normative juridical approach. The data source consists of Primarly, Interview with the judges of East jakarta religious court. Secondary, obtained books, scientific works, online mass media containing news related to the practice Child living expense execution. The study shows that religious court rulings have not provided legal protection and guarantees for the rights of children after the divorce. The child still need legal effort to earn children's living through the submission of execution, because the court could not automatically be carried out. This article identifies fundamental issues related to the execution of children's living expense after divorce, namely 1] the regulation has not strictly governed the execution, 2] the sentence of the religious court can not be executed directly, 3] the rights of the child have not been protected, 4] legal awareness of the parents,5] very complicated procedures, 6] high costs for the execution of children living expense. This study recommended that changes in law to give authority to religious court so that the verdict can be excecuted directly, affirm a father's responsibility to his child after divorce and needs to be arranged between religious courts and police officers for the verdict execution.